2021
DOI: 10.1039/d1ay01280k
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitation of three synthetic cathinones in urine by magnetic dispersive solid-phase extraction combined with DART-HRMS

Abstract: For the rapid quantitation of three synthetic cathinones, including 1-(4-Chlorophenyl)-2-(1-pyrrolidinyl)pentan-1-one (4-Cl-α-PVP), 1-(4-Methylphenyl)-2-(methylamino)pentan-1-one (4-MPD), and 1-(5,6,7,8-Tetrahydronaphthalen-2-yl)-2-(1-pyrrolidinyl)pentan-1-one (β-TH-Naphyrone), in urine, a new method was established using magnetic dispersive solid-phase extraction (MDSPE) combined...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Three matrices from different sources were adjusted by pH 7 buffer, and their pH could be adjusted to the range of pH 6.73 ± 0.04, indicating the strong adjustment ability of the buffer. The previous experiment 27 showed that stable ionization conditions could not be achieved when ethyl acetate was used as the eluent, and the elution ability of methanol and ethanol was not as good as that of acetonitrile for synthetic cathinones in MDSPE. Therefore, the effects of acetonitrile and 0.1% formic acid-acetonitrile as eluents on the analytes were investigated in this experiment.…”
Section: Instrumentation and Dart−hrms Conditionsmentioning
confidence: 97%
See 3 more Smart Citations
“…Three matrices from different sources were adjusted by pH 7 buffer, and their pH could be adjusted to the range of pH 6.73 ± 0.04, indicating the strong adjustment ability of the buffer. The previous experiment 27 showed that stable ionization conditions could not be achieved when ethyl acetate was used as the eluent, and the elution ability of methanol and ethanol was not as good as that of acetonitrile for synthetic cathinones in MDSPE. Therefore, the effects of acetonitrile and 0.1% formic acid-acetonitrile as eluents on the analytes were investigated in this experiment.…”
Section: Instrumentation and Dart−hrms Conditionsmentioning
confidence: 97%
“…MDSPE can also be equipped with an automatic extractor to process batches of samples, which makes the operation simpler, labor-saving, and more efficient. However, no studies have reported MDSPE-based methods for the determination of synthetic cathinones except our previous report …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process is time saving, low cost and environmentally friendly [16]. MSPE has been widely applied in environmental pollutant analysis [17] and drug analysis [18], especially magnetic carbon nanoparticles as the adsorbent [19]. However, there are few reports on the application of MSPE in the determination of synthetic cathinones, especially in biological matrix.…”
Section: Introductionmentioning
confidence: 99%